Platelet Function Long after Arterial and Venous Thrombosis - O’Brien, J. R; Etherington, M; Jamieson, Sandra; Klaber, M. R; Lincoln, S. V (Thrombosis and Haemostasis, 1974)
One hundred and seventeen people, including controls and patients after recovery from myocardial infarction (MI) or deep vein thrombosis (DVT) and of both sexes, have been subjected to a battery of tests thought to test platelet function. The object was to find differences which might indicate whether long-term platelet abnormalities could be demonstrated. Differences between MI and DVT results might suggest that different mechanisms are involved. The bleeding time tests were shorter in MI patients of both sexes than their respective controls and male controls have shorter bleeding times than females, but patients with DVT did not differ significantly from the controls. Tests involving platelet factor 3 and platelet factor 4 show increased activity in one or both patient groups. Thus there is considerable evidence of increased platelet/plasma activity in these disease states. The aggregation induced by thrombin was less in patients with MI and DVT than in the controls.An analysis suggests that the different groups of tests are not related and so presumably are measuring independent functions. Multiple discriminant analysis achieved for each sex moderately good separation of the three groups, namely controls, MI and DVT. These findings support the concept that there are long-term but partly differing abnormalities in MI and DVT which may predispose to thrombosis. The precise mechanisms involved need further clarification.